Coenzyme Q10 supplementation therapy for 2 children with proteinuria renal disease and ADCK4 mutation: Case reports and literature review. Issue 47 (November 2017) - Feng, Chunyue; Wang, Qiong; Wang, Jingjing; Liu, Fei; Shen, Huijun; Fu, Haidong; Mao, Jianhua
Abstract: Rationale: Mitochondrial nephropathy has a poor prognosis and often progresses to the end-stage renal disease. Renal pathology often is focal segmental glomerulosclerosis (FSGS) and does not respond to steroid therapy or immunosuppressive therapy. Some patients are benefited from the therapy of coenzyme Q10, which affect the synthesis pathway of coenzyme Q10. Patient concerns: Herein, we report 2 cases of children with proteinuria renal disease with ADCK4 mutation. Diagnoses: Proteinuria renal disease with ADCK4 mutation. Interventions: Compound heterozygous mutation in ADCK4 gene were detected with next-generation sequencing and confirmed by Sanger sequencing. Both of the patients were given coenzyme Q10 supplementation therapy. Outcomes: The first patient showed a decreased proteinuria after coenzyme Q10 supplementation therapy, while the other was not improved. Lessons: Based on the cases we reported and from the literature, recognition of ADCK4 mutation through early and accurate genetic screening could be helpful in avoiding unnecessary toxicities and in preventing complications arising in mitochondrial nephropathy.